„Nie wierz tak niedorzecznej baśni” . O tożsamości postaci „Królewny Śnieżki” Roberta Walsera i Heinza Holligera - Kornatowska, Beata (Poznańskie Studia Polonistyczne. Seria Literacka, 2022)
This article is devoted to the characters in Heinz Holliger’s opera Snow White (1998) based on Robert Walser’s dramolette (1901) of the same title. Taking into account the chronology of the plot, the analysis and interpretation focuses on the evolution of the relationships of the characters struggling with the baggage of a difficult past written in the Grimms’ fairy tale. Snow White, the Queen, the Prince and the Huntsman juggle with each other’s versions of events, swapping positions at the expense of the characters’ individual contours, succumbing to the changeability of their feelings and opinions, not stopping in their search for a post-tale identity which would allow them to coexist harmoniously. The discussion emphasises the psychoanalytical approach and criticism of language characteristic of the period in which the dramolette was written. The interpretation of the libretto is complemented by the presentation of selected musical aspects, corresponding with the character of Walser’s text and determining the final meaning of the operatic work.